2008
DOI: 10.1681/asn.2007080940
|View full text |Cite
|
Sign up to set email alerts
|

Hemopexin Induces Nephrin-Dependent Reorganization of the Actin Cytoskeleton in Podocytes

Abstract: Hemopexin is an abundant plasma protein that effectively scavenges heme. When infused into rats, hemopexin induces reversible proteinuria, and activated hemopexin is increased in children with minimal change nephrotic syndrome. These observations suggest a role for hemopexin in glomerular disease; in this study, the effects of active hemopexin on human podocytes and glomerular endothelial cells, the two cell types that compose the glomerular filtration barrier, were investigated. Within 30 min of treatment wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
88
0
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 108 publications
(89 citation statements)
references
References 39 publications
0
88
0
1
Order By: Relevance
“…Its secretion is enhanced by IL-2, IL-15, IL-12, and IL-18 and is inhibited by TGF␤1 (13). Hemopexin is a protease that activates protein kinase B and Rho A and induces nephrin-dependent reorganization of the actin cytoskeleton in cultured podocytes (14). It reduces endothelial glycocalyx and increases albumin diffusion across glomerular endothelial cell monolayers (14).…”
Section: Permeability Factors In Mcnsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its secretion is enhanced by IL-2, IL-15, IL-12, and IL-18 and is inhibited by TGF␤1 (13). Hemopexin is a protease that activates protein kinase B and Rho A and induces nephrin-dependent reorganization of the actin cytoskeleton in cultured podocytes (14). It reduces endothelial glycocalyx and increases albumin diffusion across glomerular endothelial cell monolayers (14).…”
Section: Permeability Factors In Mcnsmentioning
confidence: 99%
“…Hemopexin is a protease that activates protein kinase B and Rho A and induces nephrin-dependent reorganization of the actin cytoskeleton in cultured podocytes (14). It reduces endothelial glycocalyx and increases albumin diffusion across glomerular endothelial cell monolayers (14). Injection into rats causes proteinuria and glomerular alterations characteristic of MCNS (15).…”
Section: Permeability Factors In Mcnsmentioning
confidence: 99%
“…79 Subsequently, this group reported that 100KF/ hemopexin preparations from human serum also reduced staining of ecto-ATPases in glomeruli of kidney sections 44 as well as induced proteinuria and fusion of epithelial foot processes in glomerular capillary segments following intra-renal infusion in vivo in rats. 80 This latter observation was expanded in a recent study 24 that used cultured epithelial cells (podocytes) to provide evidence that led to the conclusion that their hemopexin preparations cause reorganization of actin fibers in podocytes through a nephrin-dependent signaling cascade. Various types of hemopexin preparations have been used in publications from the Bakker group, including recombinant hemopexin, and each merits consideration.…”
Section: Hemopexin As a Serine Proteasementioning
confidence: 98%
“…22 The NMR spectra of the recombinant proteins included in that report provide the most extensive characterization of any recombinant hemopexin yet reported. Subsequently, some authors have reported the use of recombinant human hemopexin they expressed in Pichia pastoris 23,24 or they obtained from vendors that expressed the protein in mammalian cell culture. 25 Unfortunately, these recombinant forms of hemopexin remain essentially uncharacterized.…”
Section: Recombinant Hemopexinmentioning
confidence: 99%
See 1 more Smart Citation